Enhancing Rural Enterprise Services: A Case of Small Enterprises in Khalanga Bazaar - Parajuli, Suraksha; Bhattarai, Bhishma; Raut, Bin Bahadur; Bidari, Sandesh; Aryal, Uttam (International Research Journal of MMC, 2023)
Concerns about policymakers and academics regarding the role of entrepreneurship in the socio-economic development is increasing around the world. People should be encouraged to pursue their careers in creating enterprises through practicable schemes for any societies to grow economically and sustain in the long run. Despite different components of socio-economic factors, this article is focused on ways of enhancing rural enterprise services. The method adopted was the observation and the interview and the design was descriptive. Data were collected in 2022. The findings show that education and training, access to finance, marketing and use of technology played a prominent in making an individual motivate towards entrepreneurship in rural hilly areas of Nepal. This research contributes to the academic discourse on rural enterprise development while offering actionable insights for policymakers, local communities, and entrepreneurs. By addressing the specific challenges faced by small enterprises in Khalanga Bazaar, the study aspires to inform strategies that can be extrapolated to similar rural contexts, ultimately fostering sustainable economic growth and community resilience.